Cost of a lymphedema treatment mandate: 16 years of experience in the Commonwealth of Virginia - Robert Weiss (Health Economics Review, 2022)
Background: Treatment of chronic illness accounts for over 90% of Medicare spending. Chronic lymphedema places 3-10 million Americans at risk for recurrent cellulitis. Without convincing predictions of the costs and benefits of lymphedema treatment, insurers are reluctant to fully cover treatment of this common condition. Earlier papers discussed the costs and benefits of the first 5, 7, and 10 years of a lymphedema treatment mandate in Virginia. This paper updates these costs and benefits to 16 years of experience, and includes the impacts of the Patient Protection and Affordable Care Act of 2010 and the transition to ICD-10-CM diagnostic codes in 2015. It provides added confidence that costs of a lymphedema treatment mandate are reasonable, and can result in health insurance contract savings for reduced medical visits and hospitalizations for lymphedema patients. Methods: Virginia requires annual reporting of the segregated costs of each of its 30 medical mandates. Data on Virginia's lymphedema treatment mandate for the years 2004 to 2019 have been collected from the series of annual reports. These data include actual lymphedema treatment claims data, utilization data, and claims-based estimates of the premium impact. Results: The average actual lymphedema claim cost was 2.03 per individual contract and 3.54 per group contract for the years reported, representing 0.05 and 0.08% of average total claims. The estimated premium impact was 0.16-0.32% of total average premium for all mandated coverage contracts. While lymphedema claim costs increased 3-6% per year over the study period, generally following the rise of health care costs, claim costs as a percent of average contract claims fell at a rate of 1.26-1.52% per year over that period. Medical office visits for lymphedema-related services fell from 0.10 to 0.02 visits per year per contract from the beginning to the end of the study period, and hospitalizations for lymphedema or lymphedema-related cellulitis fell to almost zero. Conclusions: The Virginia data confirmed previous conclusions that the costs of treatment of lymphedema are a small part of a typical health insurance contract, and that treatment of lymphedema by managing swelling results in lower overall medical costs and fewer hospitalizations. This is a potent model for reduction in healthcare costs while improving the quality of care for cancer survivors and others suffering with this chronic progressive condition.
Keywords: 330; Chronic disease management; Economic analysis; Health care costs; Health insurance; Insurance mandates; Lymphedema treatment costs; Medical claims; Treatment benefits